The aesthetics of anonymity on the Deep Web: : the metaphor of masks and the invisible man applied to the internet “underworld” - Abreu, Giovanna (2014)
This study addresses issues pertaining to the Deep Web as well as to the aesthetics of anonymity in this multifaceted environment of internet . From an exploratory research and a literature search, whose greatest exponents were Assange (2013), Campanelli (2010) andSibilia (2008), we tried to situate the discourses so that we could understand the contemporary subject inserted into this parallel universe and how their social relations are structured. Considering the aesthetic of anonymity, particularly in the Deep Web, we realize this inherent condition of the users is an important element, a producer of meaning. The paper also introduces a reflection on the metaphors of the masks and the invisible man as elements that prompt the understanding of the anonymity phenomenon.